2019
DOI: 10.17159/2413-3051/2019/v30i3a6356
|View full text |Cite
|
Sign up to set email alerts
|

Wind power variability during the passage of cold fronts across South Africa

Abstract: Wind is a naturally variable resource that fluctuates across timescales and, by the same token, the electricity generated by wind also fluctuates across timescales. At longer timescales, i.e., hours to days, synoptic-scale weather systems, notably cold fronts during South African winter months, are important instigators of strong wind conditions and variability in the wind resource. The variability of wind power production from aggregates of geographically disperse turbines for the passage of individual cold f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Fluctuations in renewable energy production on different time scales are strongly influenced by weather regimes and systems, like e.g., blocking regimes, low pressure systems, and the passage of fronts [78][79][80]. Inherently, so are electricity prices because of the merit-order effect.…”
Section: E the Impact Of Weather On Electricity Pricesmentioning
confidence: 99%
“…Fluctuations in renewable energy production on different time scales are strongly influenced by weather regimes and systems, like e.g., blocking regimes, low pressure systems, and the passage of fronts [78][79][80]. Inherently, so are electricity prices because of the merit-order effect.…”
Section: E the Impact Of Weather On Electricity Pricesmentioning
confidence: 99%
“…Electricity generated by wind turbines is a function of wind speed, and wind speed is variable across time scales. At longer timescales of hours to days, wind resource variability is driven by atmospheric circulation patterns and resultant synoptic-scale weather systems (Dalton et al, 2019;Kiviluoma et al, 2016). Large fluctuations in wind power within a defined timeframe are known as wind power ramps.…”
Section: Introductionmentioning
confidence: 99%
“…In a review article on the state of wind power ramp forecasting , it was found that linking ramp events to the underlying large-scale causative meteorological phenomena is important to the development or improvement of ramp forecasting frameworks. Indeed, various studies have successfully linked ramp events or wind power variability to underlying meteorological factors (Brayshaw et al, 2011;Dalton et al, 2019;Gibson & Cullen, 2015;Kalverla et al, 2017). It was however noted by that the findings from such studies are difficult to generalize to other cases and regions, as these would naturally be subject to different meteorological factors, terrains and wind farm layouts.…”
Section: Introductionmentioning
confidence: 99%